Кафка на пляже: [роман] / Харуки Мураками - Мураками Харуки (Мастера современной прозы, 2007)
Экземпляры: ф. 2 (20160810) / Инвентарный номер: 104628 / Цена: 100.00 / Авт.знак: М 91 / ГРНТИ: 17.82 / ББК: 84(5Япо)